2013
DOI: 10.1111/his.12208
|View full text |Cite
|
Sign up to set email alerts
|

Precursor‐derived versus de‐novo carcinogenesis depends on lineage‐specific mucin phenotypes of intramucosal gland‐forming gastric neoplasms

Abstract: Intramucosal adenocarcinomas of the gastric lineage may often arise de novo, develop in the proper gastric mucosa, and are partially derived from non-invasive high-grade neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…At variance, within cases immunophenotyped as intestinal, low-grade dysplasia was the most frequent (86.4 %; p = 0.001). These findings are in keeping with those recently reported by Nishimura et al [14], but differ from the results reported by Abraham et al [20]; the latter showed that intestinal-type adenomas were more likely than gastric-type adenomas to display high-grade dysplasia and adenocarcinoma in the polyps. A major difference from this study is that although the series studied by Abraham et al [20] is composed of polypoid adenomas, our series is constituted by nonpolypoid dysplasia, not including polypoid/protruded lesions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At variance, within cases immunophenotyped as intestinal, low-grade dysplasia was the most frequent (86.4 %; p = 0.001). These findings are in keeping with those recently reported by Nishimura et al [14], but differ from the results reported by Abraham et al [20]; the latter showed that intestinal-type adenomas were more likely than gastric-type adenomas to display high-grade dysplasia and adenocarcinoma in the polyps. A major difference from this study is that although the series studied by Abraham et al [20] is composed of polypoid adenomas, our series is constituted by nonpolypoid dysplasia, not including polypoid/protruded lesions.…”
Section: Discussionsupporting
confidence: 83%
“…However, evidence from the literature points to the possible existence of alternative pathways in which intestinal metaplasia may not be involved. Evidence stems mainly from the study of tiny early GCs arising in nonmetaplastic mucosa, as described by Japanese authors [14,15] as well as the studies of the expression of markers of gastric differentiation in dysplasia and gastric adenocarcinoma [7, 10, 16, 17]. The latter demonstrate that both types of lesions may express, predominantly or exclusively, markers of gastric differentiation, raising the possibility of an origin in native gastric mucosa, rather than in intestinal metaplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It means that intestinal metaplasia is not always a ‘precancerous’ lesion but a ‘paracancerous’ lesion. In our recent report, we found that early intramucosal gastric cancer lesions possessed gastric mucous phenotypes and that there is a proliferative zone with a polarity of differentiation in mucous phenotypes that is similar to the intrinsic gastric glands . Thus, it does not appear that intestinal metaplasia is a major oncogenic pathway for gastric cancer.…”
Section: Is It True That ‘Only Intestinal Metaplasia Results In Cancer’?mentioning
confidence: 95%
“…However, some EGCs do not match this histogenesis theory in clinical settings; some differentiatedtype carcinomas have been found to occur from the ordinary gastric gland mucosa without IM, in which it is especially difficult to diagnose invasion depth of the carcinoma [4][5][6][7][8][9] . Endoscopists predict submucosal invasion of EGC from the macroscopic findings of focal thickness and ulceration in the cancer lesion [14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that most EGCs conform to Nakamura's histogenesis theory, some pathologists have reported that differentiated-type carcinoma is occasionally derived from the ordinary gastric mucosa. Further, they believe that this type of lesion can be classified as gastric-type based on the mucin phenotypic expression and specific biological behavior [4][5][6][7] . By contrast, among the clinical endoscopic field, it is still difficult to assess the lateral extent and invasion depth of differentiated-type adenocarcinoma derived from the ordinary gastric mucosa before endoscopic treatment [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%